Idealny model dziennikarstwa w zderzeniu z rzeczywistością - Wąsicka, Maria (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Can one talk about an ideal model of journalism? What is meant by this term? Is journalism only a profession, or can it be a mission? These are the questions that immediately come to mind when talking about the attitudes of contemporary journalists. Who decides to do the job and for what reasons? What abilities should journalists have? Is a journalist whose popularity is growing still a journalist or does he become a celebrity? The purpose of this article is to provide answers to these questions, as well as to collect and present the characteristics that are uniquely associated with the ideal model of a journalist, and to confront them with specific, selected examples of the behavior of Polish journalists, which demonstrate that all these suggestions may be practical, but may also be only ideals divorced from reality.